Aortic aneurysm: An uncommon cause of dysphagia. (November 2022) - Suleman, Mujaheed; Pyuza, Jeremia; Sadiq, Adnan; Lodhia, Jay
Dysphagia is a serious symptom and requires urgent investigations and prompt diagnosis to initiate appropriate therapy. Dysphagia aortica is a rare entity described as difficulty in swallowing due to external compression by the aorta. The incidence of this entity is unknown. Herein we present a 90-year-old woman who presented with a progressive 3-month history of dysphagia, diagnosed with aortic aneurysm who then developed related complications and succumbed. Dysphagia aortica should be considered in the list of differential diagnoses in a patient with dysphagia although rare. Early diagnosis and management are vital to avoid poor outcomes.